Raynaud's phenomenon as an interdisciplinary problem - Karolina Górska; Aneta Szczerkowska-Dobosz; Dorota Purzycka-Bohdan; Marta Stawczyk-Macieja; Karol Wierzba; Roman J. Nowicki (Termedia Publishing House, 2017)
Raynaud's phenomenon is one of the most common disorders of the blood vessels, which usually affects fingers and toes. Raynaud's disease, also called primary Raynaud's phenomenon, is diagnosed when the cause is unknown, whereas Raynaud's syndrome or secondary Raynaud's phenomenon occurs as a skin manifestation of concomitant disease. The most common trigger is exposure to cold. Specific clinical features allow a quick diagnosis. Raynaud's phenomenon usually does not require pharmacologic treatment, but in some cases symptoms are severe and pharmacotherapy is necessary. Calcium channel blockers are usually used as a first-line treatment. Alternative forms of therapy include angiotensin-converting-enzyme inhibitors, 1-adrenergic blockers, phosphodiesterase-5 inhibitors, endothelin antagonists, nitrates, antioxidants, statins, botulinum toxin, and even autologous fat grafting.